Atrophy and hypertrophy signalling of the quadriceps and diaphragm in COPD. Issue 11 (21st October 2010) - Doucet, Mariève; Dubé, Annie; Joanisse, Denis R; Debigaré, Richard; Michaud, Annie; Paré, Marie-Ève; Vaillancourt, Rosaire; Fréchette, Éric; Maltais, François
Abstract : Background: Factors involved in the regulation of muscle mass in chronic obstructive pulmonary disease (COPD) are still poorly understood. Comparing the signalisation involved in muscle mass regulation between two muscles with different levels of activation within the same subjects is an interesting strategy to tease out the impact of local (muscle activity) versus systemic factors in the regulation of muscle mass. A study was undertaken to measure and compare the protein levels of p-AKT, AKT, Atrogin-1, p-p70S6K, p-4E-BP1, p-GSK3β as well as the mRNA expression of Atrogin-1, MuRF1 and FoxO-1 in the quadriceps and the diaphragm of 12 patients with COPD and 7 controls with normal lung function. Methods: Diaphragm biopsies were obtained during thoracic surgery and quadriceps samples were obtained from needle biopsies. Protein content and mRNA expression were measured by western blot and quantitative PCR, respectively. Results: Increased mRNA expressions of Atrogin-1, MuRF1 and FoxO-1 were found in the quadriceps compared with the diaphragm only in patients with COPD. The quadriceps/diaphragm ratio for MuRF1 was higher in COPD. The protein level of p-p70S6K was decreased in the quadriceps compared with the diaphragm in patients with COPD. The quadriceps/diaphragm ratios of p-p70S6K and p-GSK3β were lower in patients with COPD than in controls. Conclusions: These results indicate a greater susceptibility to a catabolic/anabolic imbalance favouring muscle atrophy in the quadriceps compared with the diaphragm in patients with COPD. The balance between the atrophy and hypertrophy signalling is inhomogeneous between respiratory and lower limb muscles, suggesting that local factors are likely to be involved in the regulation of muscle mass in COPD.